Effect of eccentricity on retrofitting efficiency of basalt textile reinforced concrete on partially damaged masonry columns. (15th January 2020) - Wang, Jiyang; Wan, Chenglin; Zeng, Qiang; Shen, Linghua; Malik, Muhammad Akbar; Yan, Dongming
Abstract: Retrofitting of damaged and/or ancient masonry structures is of significant importance to increase their structural safety. In this study, a retrofitting technique of basalt-textile-reinforced concrete (BTRC) was used to repair partially damaged rectangle masonry columns, and the repairing efficiency was assessed by different parameters. Compression tests with different eccentricities were conducted to explore the mechanical behaviors of initial and BTRC retrofitted masonry columns. The data in terms of crack patterns, load-displacement curves, peak load, ductility and longitudinal strains were analyzed and discussed in depth. Results show that BTRC retrofits can substantially improve the load carrying capacity and ductility of the partially damaged masonry columns under different eccentric loads that display different damage characteristics. The uniaxial constitutive (NTR-PP, NTR-PB and Sargin) models of masonry predict a relatively safe bearing capacity of BTRC-confined columns under eccentric loadings. This BTRC retrofitting technique with the features of cheap, easy-to-construct, long durability and environmental friendliness shows promising potentials in engineering applications. The findings of this study provide an effective way for repairing ancient and/or damaged masonry structures with BTRC.